Construction of Acid–Base Synergetic Sites on Mg‐bearing BEA Zeolites Triggers the Unexpected Low‐Temperature Alkylation of Phenol. Issue 6 (14th February 2017) - Xie, Jingyan; Zhuang, Wenxia; Zhang, Wei; Yan, Ning; Zhou, Yu; Wang, Jun
Abstract: Novel Mg‐bearing BEA zeolites are synthesized to simultaneously endow significantly enhanced basicity without compromising acidity over the zeolite framework. Serving as efficient solid acid–base bifunctional catalysts, they achieve the liquid‐phase selective methylation of phenol with methanol to produce o ‐ and p ‐cresol ( o / p= 2) under mild conditions. The method is readily extendable to the alkylation of phenols with various alcohols. Stereo‐ and regioselectivity (>95 % for p ‐product) was attained on the alkylation of phenol with bulky tert ‐butyl alcohol, rendering the first acid–base cooperative shape‐selective catalysis relying on the basicity of zeolites. A preliminary mechanistic analysis reveals that the remarkable activity and shape‐selectivity come from the superior special acidic–basic synergetic catalytic sites on the uniform microporous channels of the BEA zeolite. Abstract : Acid–base synergetic sites with enhanced basicity without compromising acidity are constructed on the Mg‐bearing BEA zeolite by incorporating Mg ions into the framework in a direct synthesis route. As a result, the Mg‐bearing zeolite triggers the first efficient low‐temperature liquid‐phase alkylation of phenol with high yield, stable reusability, good substrate compatibility, and unique shape selectivity.